2015
DOI: 10.1007/s00216-015-9177-1
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal solid-phase amplification system for detection of Yersinia pestis

Abstract: DNA amplification is required for most molecular diagnostic applications, but conventional polymerase chain reaction (PCR) has disadvantages for field testing. Isothermal amplification techniques are being developed to respond to this problem. One of them is the recombinase polymerase amplification (RPA) that operates at isothermal conditions without sacrificing specificity and sensitivity in easy-to-use formats. In this work, RPA was used for the optical detection of solid-phase amplification of the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 18 publications
1
38
0
Order By: Relevance
“…Whilst it was initially believed that specifically designed primers of 30e35 bases in length were necessary for RPA, there are several reports demonstrating that normal PCR primers can be used and efficient amplification achieved [5,6]. Longer primers (up to 45 nucleotides) can be used, but they could lead to secondary structures and potential primer artifacts.…”
Section: Primer Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Whilst it was initially believed that specifically designed primers of 30e35 bases in length were necessary for RPA, there are several reports demonstrating that normal PCR primers can be used and efficient amplification achieved [5,6]. Longer primers (up to 45 nucleotides) can be used, but they could lead to secondary structures and potential primer artifacts.…”
Section: Primer Designmentioning
confidence: 99%
“…In solution-phase, due to the unimpeded diffusion of primers and reaction reagents, amplification kinetics are favoured and the achieved limit of detection is subsequently usually better and amplification is achieved in a faster time than solid-phase. Nevertheless, solidphase and bridge amplification present some advantages, such as the potential for spatially resolved multiplexed amplification or the possibility to couple the amplification with diverse detection techniques including ring resonators [27e29], electrochemical [30e36] and colorimetric detection [5,6,30,33,37,38]. Several methods have been developed with solid phase amplification with performances usually inferior to that achieved with solution phase amplification [5,27e30,39] as primer accessibility is more restricted impeding amplification efficiency, and future work will need to focus on strategies to decrease amplification time.…”
Section: Solid Phase Rpamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high rate of homogenous amplifica tion, heterogeneous amplification is used more widely, because in the majority of cases, it prevents the matrix effect and allows to develop more sensitive analytical techniques. It has been also reported that heterogeneous RPA reduces non specific amplification [55].…”
Section: Amplification Techniques That Increase Analytical Signal By mentioning
confidence: 89%
“…RPA can be used in combination with various signal readout methods for detection of different pathogens, e.g., Yersinia pestis [55]. In this study, the forward primer was immobilized in the wells of enzyme immunoassay microplate, and the reverse primer was modified with biotin for binding the peroxidase streptavidin conjugate.…”
Section: Amplification Techniques That Increase Analytical Signal By mentioning
confidence: 99%